2020
DOI: 10.46661/ijeri.5120
|View full text |Cite
|
Sign up to set email alerts
|

Teachers' well-being in times of Covid-19 pandemic: factors that explain professional well-being

Abstract: This cross-sectional study was aimed to describe and analyse factors related to the professional well-being of Portuguese teachers during the COVID-19 pandemic. A previously validated, anonymous and online questionnaire was applied to a non-probabilistic sample of Portuguese teachers. In addition to the socio-demographic and professional variables, the questionnaire measured subjective and professional well-being, satisfaction with the education system and future perspectives regarding the professional circums… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
116
3
22

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(157 citation statements)
references
References 35 publications
16
116
3
22
Order By: Relevance
“…Despite the positive ratings of well-being, it should not be disregarded that primary teachers reported a plethora of factors that negatively affected their well-being. Interestingly, technical problems as reported in several other studies (Alea et al, 2020;Alves et al, 2020;Klapproth et al, 2020) did not turn out to be a major issue. Instead, work-load, social distancing and feelings of lack of competence and self-efficacy were among the most aversive aspects of distance teaching.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…Despite the positive ratings of well-being, it should not be disregarded that primary teachers reported a plethora of factors that negatively affected their well-being. Interestingly, technical problems as reported in several other studies (Alea et al, 2020;Alves et al, 2020;Klapproth et al, 2020) did not turn out to be a major issue. Instead, work-load, social distancing and feelings of lack of competence and self-efficacy were among the most aversive aspects of distance teaching.…”
Section: Discussionsupporting
confidence: 48%
“…Having left student development and learning to chance could deteriorate teacher well-being. Alves et al (2020) asked Portuguese teachers during the pandemic to compare their current professional well-being to their well-being before the pandemic. Data from 1479 teachers indicated a decrease in emotional well-being (more stressed, more tired, more work overloaded, more anxious, more pressed and more distressed along with feeling less satisfied, less motivated, less valued) and an increase in teaching difficulties regarding distance learning, use of digital platforms, and evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that teachers at elder age and more years of service are prone to elevated levels of emotional exhaustion, and lower levels of well-being [ 62 , 63 ]. In our study, the participants median age was 46 with average of 17 years in the teaching profession.…”
Section: Discussionmentioning
confidence: 99%
“…Focusing on well-being and resilience under these circumstances was also found to be a key to success in a study of South African lecturers [ 26 ]. In Portugal, a study analysing variables related to the professional well-being of Portuguese teachers during the COVID-19 pandemic found that ongoing monitoring of teachers’ well-being throughout their careers is essential to help them cope with the pandemic [ 27 ]. The mediating role of subjective well-being in job burnout is well known, as is the association of poor well-being with high levels of burnout [ 28 ].…”
Section: Introductionmentioning
confidence: 99%